2008
DOI: 10.1186/1751-0759-2-14
|View full text |Cite
|
Sign up to set email alerts
|

Stress and psychological factors before a migraine attack: A time-based analysis

Abstract: Background: The objective of this study is to examine the stress and mood changes of Japanese subjects over the 1-3 days before a migraine headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
4
28
0
Order By: Relevance
“…These results are consistent with and extend prior research. [11][12][13][14][15][16][17][18][19][20] In aggregate, these findings and the prior literature support the let-down hypothesis, which predicts that decline in perceived stress is associated with an increased probability of migraine onset. There are at least 2 alternative mechanisms to explain this phenomenon.…”
supporting
confidence: 73%
See 4 more Smart Citations
“…These results are consistent with and extend prior research. [11][12][13][14][15][16][17][18][19][20] In aggregate, these findings and the prior literature support the let-down hypothesis, which predicts that decline in perceived stress is associated with an increased probability of migraine onset. There are at least 2 alternative mechanisms to explain this phenomenon.…”
supporting
confidence: 73%
“…Trigger factors, measurable precipitants associated with an increased probability of an attack, can include stressful events, hormonal changes, weather changes, and certain foods, although some studies demonstrate reduced odds for migraine attacks in relation to certain variables. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] In patient surveys, perceived stress was associated with migraine onset in up to 80% of respondents. [13][14][15][16] Diary studies have shown that "daily hassles" significantly increase in the 2-to 3-day period before a migraine day.…”
Section: Objectivementioning
confidence: 99%
See 3 more Smart Citations